Ricci flow of homogeneous manifolds - Lauret, Jorge Ruben (2013)
We present in this paper a general approach to study the Ricci flow on homogeneous manifolds. Our main tool is a dynamical system defined on a subset Hq,n of the variety of (q+n)-dimensional Lie algebras, parameterizing the space of all simply connected homogeneous spaces of dimension n with a q-dimensional isotropy, which is proved to be equivalent in a precise sense to the Ricci flow. The approach is useful to better visualize the possible (nonflat) pointed limits of Ricci flow solutions, under diverse rescalings, as well as to determine the type of the possible singularities. Ancient solutions arise naturally from the qualitative analysis of the evolution equation. We develop two examples in detail: a 2-parameter subspace of H1,3 reaching most of 3-dimensional geometries, and a 2-parameter family in H0,n of left-invariant metrics on n-dimensional compact and non-compact semisimple Lie groups.